TEMPORAL ANALYSIS OF AIR POLLUTANTS (NO2, GROUND-LEVEL O3, AND CO) AND THEIR RELATIONSHIP TO AIR TEMPERATURE AND SOLAR RADIATION IN LIMA METROPOLITANA - Benites-Morales, Orlando Fernando (2023)
This study includes the temporal analysis of the levels of NO2, CO, and ground-level O3 measured in Lima Metropolitana between the years 2015 to 2018 and the relationship between them and with air temperature and solar radiation. For this, descriptive, correlational, and regression temporal analyzes were carried out using hourly records taken in different areas of the city. The levels of the gases evaluated were mainly below the Peruvian regulations and the World Health Organization's air quality guidelines, so their influence on the health of the population was not relevant. The hourly levels of these gases were bimodal and were influenced by vehicular traffic for NO2 and CO, and by solar radiation for ground-level O3; although, the latter may also have been influenced by its nocturnal movement. Daily behavior showed the so-called "weekend effect". The correlation analysis indicated a homogeneous behavior of the parameters between the evaluated areas; plus, there was a negative correlation between CO and ground-level O3. Furthermore, there was a positive correlation between NO2 and CO; and between the meteorological factors with NO2 and ground-level O3. Finally, multiple linear regression models were generated that adequately estimated the historical values of ground-level O3. Key words: NO2, CO, ground-level O3, air temperature, solar radiation, vehicular traffic, temporal analysis, Lima Metropolitana area.